2017
DOI: 10.4236/gep.2017.512010
|View full text |Cite
|
Sign up to set email alerts
|

A Rainfall Intensity-Duration Threshold for Mass Movement in Badulla, Sri Lanka

Abstract: Mass movement in Sri Lanka is mainly triggered by heavy rainfall. International literature is rich of works defining rainfall intensity-duration models to identify the rainfall threshold for various types of Mass movement. However, studies have not focused to establish a relationship between intensity and duration of rainfall in Sri Lanka. Therefore, this study focused to establish rainfall intensity-duration models to identify the rainfall threshold for mass movements in Badulla district in Sri Lanka, where f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Available dominant rock types, crystallization process are the main factors that regulate the chemical composition and physical properties of surface water [14]. Badulu Oya catchment being located in the intermediate zone on the leeward side of Central Highlands receives an average 2000 mm comparatively low rainfall [15]. The catchment receives high rainfall during October to November and December to February second inter monsoon and during North East monsoon periods.…”
Section: Discussionmentioning
confidence: 99%
“…Available dominant rock types, crystallization process are the main factors that regulate the chemical composition and physical properties of surface water [14]. Badulu Oya catchment being located in the intermediate zone on the leeward side of Central Highlands receives an average 2000 mm comparatively low rainfall [15]. The catchment receives high rainfall during October to November and December to February second inter monsoon and during North East monsoon periods.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery was assumed as a function of emergency recovery (ER), infrastructure resettlement (IR) and long-term recovery (LtR). There might be several factors (performance Indicator) that could be assumed to affect in positive and negative mean on dependent variables of ER, IR and LtR as shown in Table 1 [4,8,14].…”
Section: Methodsmentioning
confidence: 99%
“…However, increase of frequency and severity of landslides in Sri Lanka, attention on landslide recovery becomes more significant and complicated [8]. The landslide recovery process is often long, costly and complex, and the responsibilities of the recovery project distributed among numerous sectors and stakeholders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by the NBRO have revealed that nearly 70% of the landslides that occurred in populated areas in Sri Lanka are human-induced [4]. As a result, the frequency and severity of landslides in the country have increased in the recent past, which is in line with global trends [5][6][7]. Scientists therefore mostly focus on promoting landslide risk mitigation measures at local and global scales based on the available landslide information.…”
Section: Introductionmentioning
confidence: 99%